Chemically monoubiquitinated PEX5 binds to the components of the peroxisomal docking and export machinery - Hagmann, Vera (Sci Rep, 2018)
Peroxisomal matrix proteins contain either a peroxisomal targeting sequence 1 (PTS1) or a PTS2 that are recognized by the import receptors PEX5 and PEX7, respectively. PEX5 transports the PTS1 proteins and the PEX7/PTS2 complex to the docking translocation module (DTM) at the peroxisomal membrane. After cargo release PEX5 is monoubiquitinated and extracted from the peroxisomal membrane by the receptor export machinery (REM) comprising PEX26 and the AAA ATPases PEX1 and PEX6. Here, we investigated the protein interactions of monoubiquitinated PEX5 with the docking proteins PEX13, PEX14 and the REM. “Click” chemistry was used to synthesise monoubiquitinated recombinant PEX5. We found that monoubiquitinated PEX5 binds the PEX7/PTS2 complex and restores PTS2 protein import in vivo in ΔPEX5 fibroblasts. In vitro pull-down assays revealed an interaction of recombinant PEX5 and monoubiquitinated PEX5 with PEX13, PEX14 and with the REM components PEX1, PEX6 and PEX26. The interactions with the docking proteins were independent of the PEX5 ubiquitination status whereas the interactions with the REM components were increased when PEX5 is ubiquitinated.